Analisis Tingkat Kesehatan Bank Umum Konvensional di ASEAN dengan Metode RGEC Pasca Pandemi Covid-19 - Wulandari, Cynthia; Indrabudiman, Amir (Jurnal Disrupsi Bisnis, 2024)
This study aims to analyze the differences in Risk Profile, Good Corporate Governance, Earning and Capital in Banks in Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam during 2022 with the number of research samples being 80 Conventional Commercial Banks selected through the purposive sampling method. The analysis technique uses ANOVA difference test with software Microsoft Excel 2019, Jamovi version 2.3.28 and SPSS version 22. The results of this study found that there were not significant differences in the average level of Risk Profile, Good Corporate Governance, Earning and Capital in each Bank in Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam.